Long term follow-up of heart rate variability in healthcare workers with mild COVID-19 - Liviero, Filippo; Scapellato, Maria Luisa; Volpin, Anna; Battistella, Monica; Fabris, Laura; Brischigliaro, Laura; Folino, Franco; Moretto, Angelo; Mason, Paola; Pavanello, Sofia (Frontiers in Neurology, 2024)
Prior investigations into post-COVID dysautonomia often lacked control groups or compared affected individuals solely to healthy volunteers. In addition, no data on the follow-up of patients with SARS-CoV-2-related autonomic imbalance are available. In this study, we conducted a comprehensive clinical and functional follow-up on healthcare workers (HCWs) with former mild COVID-19 (group 1, n=67), to delineate the trajectory of post-acute autonomic imbalance, we previously detected in a case-control study. Additionally, we assessed HCWs for which a test before SARS-CoV-2 infection was available (group 2, n=29), who later contracted SARS-CoV-2, aiming to validate findings from our prior case-control investigation. We evaluated autonomic nervous system heart modulation activity by means of time and frequency domain heart rate variability analysis (HRV) in HCWs during health surveillance visits. Short-term electrocardiogram (ECG) recordings, were obtained at about 6, 13 months and both at 6 and 13 months from the negative SARS-CoV-2 naso-pharyngeal swab (NPS) for group 1 and at about 1-month from the negative NPS for group 2. HCWs who used drugs, had comorbidities that affected HRV, or were hospitalized with severe COVID-19 were excluded. Group 1 was split into three subgroups clinically and functionally followed at, about 6 months (subgroup-A, n=17), 13 months (subgroup-B, n=37) and both at 6 and 13 months (subgroup-C, n=13) from the negative SARS-CoV-2 NPS. In subgroup-A,